Strange Bedfellows (University of Groningen Press, 2024)
‘Interdisciplinarity’ is a bit of a buzzword in the Dutch university sector. It is also one of the most prioritized policy goals at a national and European level. Yet, ‘interdisciplinarity’ remains under-defined, and the challenges and obstacles unique to doing interdisciplinarity remain fuzzy. How, then, are we supposed to adopt an interdisciplinary approach if we don’t even know what the word means?